Open Ankle Fractures: What Predicts Infection? A Multicenter Study. Issue 1 (January 2022) - Cooke, Margaret E.; Tornetta, Paul; Firoozabadi, Reza; Vallier, Heather; Weinberg, Douglas S.; Alton, Timothy B.; Dillman, Megan R.; Westberg, Jerald R.; Schmidt, Andrew; Bosse, Michael; Leas, Daniel P.; Archdeacon, Michael; et al.
Abstract : Objective: To identify the patient, injury, and treatment factors associated with an acute infection during the treatment of open ankle fractures in a large multicenter retrospective review. To evaluate the effect of infectious complications on the rates of nonunion, malunion, and loss of reduction. Design: Multicenter retrospective review. Setting: Sixteen trauma centers. Patients: One thousand and 3 consecutive skeletally mature patients (514 men and 489 women) with open ankle fractures. Main Outcome Measures: Fracture-related infection (FRI) in open ankle fractures. Results: The charts of 1003 consecutive patients were reviewed, and 712 patients (357 women and 355 men) had at least 12 weeks of clinical follow-up. Their average age was 50 years (range 16–96), and average BMI was 31; they sustained OTA/AO types 44A (12%), 44B (58%), and 44C (30%) open ankle fractures. The rate FRI rate was 15%. A multivariable regression analysis identified male sex, diabetes, smoking, immunosuppressant use, time to wound closure, and wound location as independent risk factors for infection. There were 77 cases of malunion, nonunion, loss of reduction, and/or implant failure; FRI was associated with higher rates of these complications ( P = 0.01). Conclusions: Several patient, injury, and surgical factors were associated with FRI in the treatment of open ankle fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.